Drug policy, harm reduction & research in Ireland, 1996-2008 - Quigley, Eoghan Kevin (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2010)
This study is part of the small body of general documentary research concerned with examining different aspects and features of Irish drug policy. While the contemporary history of Irish drug policy has been characterised by a great deal of developments there has been a limited documentary analysis of these events. This study explores events during the years 1996 to 2008. It was concerned with documenting and examining some of the main developments that occurred during these years in policy, the treatment system, and the role of research in these changes. It looked at the international context in which these events were set and explored the defining features of drug policy during this time. In addition, the study discussed the work of indigenous research bodies, as well as developments in parts of the treatment system. It was largely focused on the evolving public health response to challenges posed by the human immunodeficiency virus (HIV) and injecting drug use (IDU).
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin